Phytonanofabrication of iron oxide particles from the Acacia jacquemontii plant and their potential application for the removal of brilliant green and Congo red dye from wastewater - Patel, Shreya; Desai, Reema; Patel, Bhakti; Ali, Daoud; Dawane, Vinars; Gadhvi, Kamlesh; Yadav, Virendra Kumar; Choudhary, Nisha; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Bioengineering and Biotechnology, 2023)
Phytonanofabrication is one of the most promising areas that has drawn the attention of scientists worldwide due to its eco-friendly nature and biocompatibility. In the current investigation, we reported the phyto-assisted formation of iron oxide nanoparticles (IONPs) from a rare species of Acacia (Acacia jacquemontii). First, ethanolic extracts of the stem powder were analyzed by high-performance thin-layer chromatography (HPTLC) for the identification of phytochemicals in the stem sections of Acacia. Furthermore, IONPs were synthesized by a chemical co-precipitation method by using the stem extract. The phytonanofabricated iron oxide particles were investigated by UV–Vis spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and Energy-dispersive X-ray spectroscopy (EDS) for elemental analysis. HPTLC confirmed the presence of several phenols and terpenoids in the ethanolic extracts of the stem. UV–Vis spectroscopy exhibited an absorbance peak at 380 nm, indicating the formation of IONPs, while FTIR spectroscopy showed the typical bands for Fe-O in the range of 599–1,000 cm−1 in addition to several functional groups of organic molecules at 1,596 cm−1, 2,313 cm−1, and 3,573 cm−1. XRD exhibits the amorphous nature of IONPs with peaks at 30.7, 35.5, and 62.7 nm. The IONPs were spherical-shaped, whose size varies from 10 to 70 nm, as confirmed by FESEM. EDS exhibited the presence of Fe, O, C, and NaCl. Finally, the phytonanofabricated iron oxide particles were utilized for the removal of brilliant green (BG) and Congo red (CR) dye from the aqueous solution. The removal efficiency of BG dye was up to 54.28%, while that of Congo red dye was up to 36.72% in 120 min and 60 min, respectively. Furthermore, the effect of pH and contact time was also assessed on both the dyes, where CR exhibited maximum removal at acidic pH, i.e., 47.5%, while BG showed maximum removal at pH 10, i.e., 76.59%.